Laminate

JP7645876B2Active Publication Date: 2025-03-14KURARAY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022517053
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-22
Filing Date
2021-04-20
Publication Date
2025-03-14
Estimated Expiration
2041-04-20

AI Technical Summary

Benefits of technology

【0008】 本発明の積層体は、高温高湿下における反りの発生が少なく、表面硬度、耐候性が良好である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007645876000001
    Figure 0007645876000001
  • Figure 0007645876000002
    Figure 0007645876000002
  • Figure 0007645876000003
    Figure 0007645876000003
Patent Text Reader

Abstract

The present invention provides a laminate provided with a layer comprising: a resin composition (I) containing 40 to 87 wt. % of a methyl methacrylate unit, 6 to 30 wt. % of a structural unit (R) having, on a main chain, at least one cyclic structure selected from the group consisting of a glutaric acid anhydride unit and an N-substituted or unsubstituted glutarimide unit, and 51 wt. % or more of an acrylic copolymer (A) having 7 to 30 wt. % of an α-methylstyrene unit; and a layer comprising a resin composition (T) containing polycarbonate.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate comprising a layer made of a resin composition containing an acrylic copolymer and a layer made of a resin composition containing a polycarbonate. [Background technology]

[0002] Methacrylic resins are excellent in transparency, scratch resistance, weather resistance, etc. On the other hand, polycarbonates are excellent in impact resistance, etc. A laminate including a layer containing a methacrylic resin and a layer containing a polycarbonate is excellent in transparency, scratch resistance, weather resistance, impact resistance, etc., and is used for surface members of house walls, furniture, home appliances, electronic devices, display devices, etc.

[0003] The above-mentioned laminate is prone to warping when exposed to high temperature or high humidity for a long time, which may cause problems in the usage environment. To solve such problems, it is effective to improve the heat resistance and moisture resistance of the methacrylic resin, and as a specific measure, a method of including a structural unit having a ring skeleton in a layer containing the methacrylic resin has been proposed. Patent Document 1 discloses a laminate comprising a layer made of a methacrylic resin having a glass transition temperature of 110°C or higher, which contains a methyl methacrylate unit, a methacrylic acid unit, an acrylic acid unit, a maleic anhydride unit, an N-substituted or unsubstituted maleimide unit, a glutaric anhydride structural unit, and a unit selected from a glutarimide structural unit, and a layer made of polycarbonate. Patent Document 2 discloses a laminate comprising a layer made of a methacrylic resin having a glass transition temperature of 120 to 180°C, which contains a structural unit derived from a methacrylic acid ester having an alicyclic hydrocarbon group, and a layer made of polycarbonate. Patent Document 3 discloses a laminate comprising a layer made of a vinyl copolymer resin having (meth)acrylic acid ester structural units and aliphatic vinyl structural units in which 70% or more of aromatic double bonds derived from an aromatic vinyl monomer are hydrogenated, and a layer made of polycarbonate. Patent Document 4 discloses a laminate comprising a layer made of a resin composition containing a methacrylic resin and an SMA resin (a copolymer resin made of styrene and maleic anhydride), and a layer made of polycarbonate. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent Publication No. 2009-248416 [Patent Document 2] International Publication No. 2014 / 050136 [Patent Document 3] International Publication No. 2011 / 145630 [Patent Document 4] International Publication No. 2015 / 050051 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the laminates obtained by these methods have a problem that the surface hardness and weather resistance are reduced due to the inclusion of structural units having a ring skeleton. By reducing the composition ratio of the structural units having a ring skeleton, the reduction in surface hardness and weather resistance can be suppressed, but the glass transition temperature of the obtained resin composition becomes insufficient.

[0006] The present invention has been made in view of the above problems, and an object of the present invention is to provide a laminate including a layer made of a resin composition containing an acrylic copolymer and a layer containing a polycarbonate, which is less prone to warping under high temperature and high humidity conditions and has excellent surface hardness and chemical resistance. [Means for solving the problem]

[0007] As a result of investigations conducted in order to achieve the above object, the present invention has been completed, which includes the following aspects. [1] A laminate comprising: a layer made of a resin composition (I) containing 51 mass% or more of an acrylic copolymer (A) having 30 to 87 mass% of methyl methacrylate units, 6 to 40 mass% of structural units (R) having at least one ring structure in the main chain selected from the group consisting of glutaric anhydride units and N-substituted or unsubstituted glutarimide units, and 7 to 30 mass% of α-methylstyrene units; and a layer made of a resin composition (T) containing a polycarbonate. [2] The laminate according to [1], wherein the structural unit (R) is an N-substituted or unsubstituted glutarimide unit represented by formula (QI). [ka] (In formula (QI), R 1 are each independently a hydrogen atom or a methyl group, R 2 is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring. [3] The laminate according to [1] or [2], wherein the resin composition (I) contains 1 to 49 mass % of a multilayer copolymer elastomer (B-1) having a methacrylic acid ester unit and an acrylic acid ester unit. [4] The laminate according to [1] or [2], characterized in that the resin composition (I) contains 1 to 49 mass% of a block copolymer elastomer (B-2) consisting of a polymer block (b1) having a methacrylic acid ester unit and a polymer block (b2) having an acrylic acid ester unit. [5] The laminate according to [1] or [2], wherein the resin composition (I) contains 1 to 49 mass % of a methacrylic resin (C). [6] The laminate according to any one of [1] to [5], wherein the absolute value of the difference in glass transition temperature between the resin composition (I) and the resin composition (T) is 30°C or less, and the absolute value of the difference in saturated water absorption between the resin composition (I) and the resin composition (T) is 2% or less. [7] The laminate according to any one of [1] to [6], wherein the thickness of the layer made of the resin composition (I) is 2 to 15% of the total thickness of the laminate. [8] The laminate according to any one of [1] to [6], which has a layer made of the resin composition (I) on at least one surface. [9] The laminate according to any one of [1] to [8], further comprising an abrasion-resistant layer on at least one surface. Effect of the Invention

[0008] The laminate of the present invention is less susceptible to warping under high temperature and high humidity conditions, and has good surface hardness and weather resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] [Resin composition (I)] The resin composition (I) contains an acrylic copolymer (A). In one preferred embodiment, the resin composition (I) contains an acrylic copolymer (A) and, if necessary, an elastomer (B) and / or a methacrylic resin (C). The elastomer (B) may be a multilayer copolymer elastomer (B-1) or a block copolymer elastomer (B-2). The content of the acrylic copolymer (A) in the resin composition (I) is 51 mass% or more, preferably 65 mass% or more, more preferably 80 mass% or more, and even more preferably 90 mass% or more, and the resin composition (I) may be composed only of the acrylic copolymer (A).

[0010] (Acrylic copolymer (A)) The acrylic copolymer (A) according to the present invention contains methyl methacrylate units, α-methylstyrene units, and structural units (R). The acrylic copolymer (A) according to the present invention has a ratio of methyl methacrylate units of 30 to 87% by mass, preferably 40 to 85% by mass, and more preferably 50 to 80% by mass, based on the total structural units. If the ratio of methyl methacrylate units is less than this range, the total light transmittance of the resulting acrylic copolymer is deteriorated, whereas if the ratio of methyl methacrylate units is more than this range, the heat resistance of the resulting acrylic copolymer is reduced.

[0011] The acrylic copolymer (A) according to the present invention has an α-methylstyrene unit content of 7-30% by mass, preferably 8-27% by mass, more preferably 11-25% by mass, based on the total structural units. If the content of α-methylstyrene units is less than this range, the saturated water absorption of the resulting acrylic copolymer will be high. In addition, an acrylic copolymer having an α-methylstyrene unit content of more than 30% by mass will have low polymerizability and low productivity.

[0012] The structural unit (R) is a structural unit having at least one ring structure in the main chain selected from the group consisting of a glutaric anhydride unit and an N-substituted or unsubstituted glutarimide unit.

[0013] The glutaric anhydride unit is a unit having a 2,6-dioxodihydropyrandiyl structure. An example of the unit having a 2,6-dioxodihydropyrandiyl structure is a structural unit represented by the formula (QII).

[0014] [ka] In formula (QII), R 3 are each independently a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and two R 3 and are preferably both methyl groups.

[0015] The unit having a 2,6-dioxodihydropyrandiyl structure can be incorporated into the acrylic copolymer by the method described in JP 2007-197703 A, JP 2010-96919 A, etc., for example, intramolecular cyclization of two adjacent structural units derived from (meth)acrylic acid, intramolecular cyclization of a structural unit derived from (meth)acrylic acid and a structural unit derived from methyl (meth)acrylate, etc. JP 2007-197703 A and JP 2010-96919 A ​​are incorporated herein by reference in their entirety.

[0016] The N-substituted or unsubstituted glutarimide unit is a unit having an N-substituted or unsubstituted 2,6-dioxopiperidinediyl structure. An example of a unit having an N-substituted or unsubstituted 2,6-dioxopiperidinediyl structure is a structural unit represented by formula (QI).

[0017] [ka] In formula (QI), R 1 are each independently a hydrogen atom or a methyl group, and two R 1 Preferably, both R are methyl groups. 2is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring, and is preferably a hydrogen atom, a methyl group, an n-butyl group, a cyclohexyl group, or a benzyl group, and more preferably a methyl group, an n-butyl group, or a cyclohexyl group. The structural unit represented by formula (QI) can be prepared by reacting the corresponding acid anhydride (Q IIa) and R as shown in scheme (i), for example. 2 It may be produced by the reaction of an imidizing agent represented by NH2, or by the intramolecular cyclization reaction of a copolymer having a partial structure of formula (QIII). It is preferable to heat the copolymer to convert the structural unit represented by formula (QIII) to the structural unit represented by formula (QI) by the intramolecular cyclization reaction. Scheme (i) [ka] (In the formula, R 1 , R 2 is as defined above.)

[0018] The N-substituted or unsubstituted glutarimide unit can be obtained by the methods described in WO2005 / 10838A1, JP2010-254742A, JP2008-273140A, JP2008-274187A, and the like, specifically, by reacting a structural unit derived from two adjacent methyl methacrylates or a glutaric anhydride unit with an imidizing agent such as ammonia, methylamine, ethylamine, n-propylamine, isopropylamine, n-butylamine, isobutylamine, tert-butylamine, n-hexylamine, and other aliphatic hydrocarbon group-containing amines, aniline, toluidine, trichloroaniline, and other aromatic hydrocarbon group-containing amines, cyclohexylamine, and other alicyclic hydrocarbon group-containing amines, urea, 1,3-dimethylurea, 1,3-diethylurea, 1,3-dipropylurea, and the like. Among these, ammonia, methylamine, n-butylamine, cyclohexylamine and benzylamine are preferred, more preferably methylamine, n-butylamine and cyclohexylamine groups, and even more preferably methylamine. During this imidization reaction, some of the methyl methacrylate units may be hydrolyzed to carboxyl groups, and these carboxyl groups are preferably converted back to the original methyl methacrylate units by reaction with dimethyl carbonate. WO2005 / 10838A1, JP2010-254742A, JP2008-273140A, and JP2008-274187A are incorporated herein by reference in their entirety.

[0019] The acrylic copolymer (A) according to the present invention has a ratio of the structural unit (R) of 6 to 40% by mass, preferably 7 to 38% by mass, more preferably 8 to 35% by mass, based on the total structural units. The orientation birefringence of the acrylic copolymer can be changed by changing the ratio of the structural unit (R) to methyl methacrylate. In addition, the higher the content of the structural unit (R), the more the heat resistance of the acrylic copolymer improves, but the more the flexibility decreases, and the compatibility with other copolymers and the moldability tend to decrease.

[0020] The acrylic copolymer (A) according to the present invention may contain a structural unit (O) other than the methyl methacrylate unit, the α-methylstyrene unit, and the (R). Examples of the structural unit (O) include structural units derived from vinyl monomers having only one polymerizable carbon-carbon double bond in one molecule, such as (meth)acrylamide, (meth)acrylonitrile, (meth)acrylic acid, and styrene; structural units derived from cyclic acid anhydrides, such as maleic anhydride, citraconic anhydride, and dimethylmaleic anhydride; and structural units derived from N-substituted maleimides, such as N-methylmaleimide, N-phenylmaleimide, N-benzylmaleimide, and N-cyclohexylmaleimide. Of these, styrene is preferred. The proportion of the structural unit (O) is preferably 2% by mass or more and 20% by mass or less, more preferably 5% by mass or more and 10% by mass or less, based on the total structural units. The proportions of the methyl methacrylate unit, the α-methylstyrene unit, the structural unit (R), and the structural unit (O) are as follows: 1 H-NMR, 13 It can be measured by C-NMR, etc.

[0021] The acrylic copolymer (A) according to the present invention has a weight average molecular weight (Mw) of preferably 40,000 to 200,000, more preferably 50,000 to 180,000, and further preferably 55,000 to 160,000. When Mw is 40,000 or more, the strength, toughness, etc. of the molded article of the present invention are improved. When Mw is 200,000 or less, the flowability is improved, and molding processability is improved.

[0022] The weight average molecular weight (Mw) is a value calculated by converting a chromatogram measured by gel permeation chromatography into the molecular weight of standard polystyrene.

[0023] The acrylic copolymer (A) according to the present invention has an acid value of preferably 0.01 to 0.30 mmol / g, more preferably 0.05 to 0.28 mmol / g. The acid value is a value proportional to the content of carboxylic acid units and carboxylic anhydride units in the acrylic copolymer. The acid value can be calculated, for example, by the method described in JP-A-2005-23272. When the acid value is within the above range, the balance of heat resistance, mechanical properties, and moldability is excellent.

[0024] The acrylic copolymer (A) according to the present invention has a glass transition temperature of preferably 130°C as a lower limit, more preferably 131°C, and even more preferably 132°C as an upper limit, and is not particularly limited, but is preferably 160°C. In this specification, the "glass transition temperature (Tg)" is measured in accordance with JIS K7121. Specifically, the temperature is raised once to 230°C, then cooled to room temperature, and then the DSC curve is measured under conditions of raising the temperature from room temperature to 230°C at a rate of 10°C / min. The midpoint determined from the DSC curve measured during the second heating is determined as the "glass transition temperature (Tg)".

[0025] The saturated water absorption of the acrylic copolymer (A) according to the present invention can be measured under the following conditions. The acrylic copolymer is press-molded into a sheet having a thickness of 1.0 mm. A test piece of 50 mm x 50 mm is cut out from the center of the obtained press-molded sheet and dried in a dryer at 80 ° C for 16 hours or more. The dried test piece is cooled to room temperature in a desiccator, and then its weight is measured to the nearest 0.1 mg, and this weight is defined as the initial weight Wo. The test piece is immersed in distilled water at 23 ° C., and after immersion for 24 hours, the test piece is removed from the water and all surface moisture is wiped off with a clean, dry cloth or filter paper. Within 1 minute of removing from the water, the test piece is weighed again to the nearest 0.1 mg. The test piece is immersed again, and the weight is measured again in the same manner as above after 24 hours. The weight when the weight change rate of the test piece becomes within 0.02% of Wo is defined as the saturated weight Ws. The saturated water absorption can be calculated from formula (2).

[0026]

number

[0027] The acrylic copolymer (A) according to the present invention has a 1% thermal weight loss temperature in a nitrogen atmosphere of preferably 265° C. or higher, more preferably 270° C. or higher. The 1% thermal weight loss temperature can be measured using a thermogravimetric analyzer (TGA). The 1% thermal weight loss temperature can be determined as the temperature at which the weight loss is 1% relative to the charged weight.

[0028] The acrylic copolymer (A) according to the present invention can be obtained by a method including subjecting a copolymer of methyl methacrylate and α-methylstyrene (hereinafter sometimes referred to as a precursor polymer) to a ring structure-forming reaction. That is, the method for producing the acrylic copolymer (A) comprises the steps of: continuously supplying a reaction raw material containing a monomer mixture containing 70 to 93 mass % of methyl methacrylate, 30 to 7 mass % of α-methylstyrene, and 0 to 10 mass % of a copolymerizable monomer, a radical polymerization initiator, and optionally a chain transfer agent, to a tank reactor; bulk polymerizing the monomer mixture in the tank reactor to a polymerization conversion rate of 30 to 60 mass % to obtain a reaction product; and removing the monomer mixture from the reaction product to obtain a precursor polymer. The method includes a step of subjecting the obtained precursor polymer to a ring structure forming reaction, and each step can be carried out by a known technique. The copolymerizable monomer can form the structural unit (O).

[0029] (Multilayer copolymer elastomer (B-1)) The laminate of the present invention preferably contains a multilayer copolymer elastomer (B-1) having a methacrylic acid ester unit and an acrylic acid ester unit in the layer made of the resin composition (I). The content of the multilayer copolymer elastomer (B-1) in the resin composition (I) is preferably 1 to 49 mass%, more preferably 5 to 45 mass%, and further preferably in the range of 10 to 40 mass%. The laminate of the present invention has improved brittleness by containing the multilayer copolymer elastomer (B-1) in the range of 1 to 49 mass%.

[0030] The multi-layer copolymer elastomer may be one that is made of an outermost layer made of a thermoplastic polymer (B-1-III) and an inner layer made of a cross-linked polymer that is in contact with and covers the outermost layer.The multi-layer copolymer elastomer may be, for example, a two-layer polymer elastomer in which the core (inner layer) is a cross-linked rubber polymer (B-1-II) and the outer shell (outermost layer) is a thermoplastic polymer (B-1-III), a three-layer polymer elastomer in which the core (inner layer) is a cross-linked polymer (B-1-I) and the inner shell (inner layer) is a cross-linked rubber polymer (B-1-II) and the outer shell (outermost layer) is a thermoplastic polymer (B-1-III), or a four-layer polymer elastomer in which the core (inner layer) is a cross-linked rubber polymer (B-1-II) and the first inner shell (inner layer) is a cross-linked polymer (B-1-I) and the second inner shell (inner layer) is a cross-linked rubber polymer (B-1-II) and the outer shell (outermost layer) is a thermoplastic polymer (B-1-III).

[0031] From the viewpoint of transparency, it is preferable to select the polymers contained in each layer so that the difference in refractive index between adjacent layers is preferably less than 0.005, more preferably less than 0.004, and even more preferably less than 0.003.

[0032] The mass ratio of the inner layer to the outermost layer in the multilayer copolymer elastomer is preferably 60 / 40 to 95 / 5, more preferably 70 / 30 to 90 / 10. The proportion of the layer containing the crosslinked rubber polymer (B-1-II) in the inner layer is preferably 20 to 70 mass%, more preferably 30 to 50 mass%.

[0033] The multilayer copolymer elastomer has an average particle size of preferably 0.05 to 3 μm, more preferably 0.1 to 2 μm, and even more preferably 0.2 to 1 μm. By using a multilayer copolymer elastomer having an average particle size within such range, particularly an average particle size of 0.2 to 1 μm, toughness can be exhibited even with a small amount of the elastomer, and therefore rigidity and surface hardness are not impaired. The average particle size in this specification is the average value in the particle size distribution based on volume measured by a light scattering method.

[0034] The thermoplastic polymer (B-1-III) is a polymer comprising methacrylic acid alkyl ester units having an alkyl group having 1 to 8 carbon atoms and, if necessary, monofunctional monomer units other than the methacrylic acid alkyl esters. It is preferable that the thermoplastic polymer (B-1-III) does not contain polyfunctional monomer units.

[0035] The amount of the methacrylic acid alkyl ester units having an alkyl group having 1 to 8 carbon atoms constituting the thermoplastic polymer (B-1-III) is preferably 80 to 100 mass %, more preferably 85 to 95 mass %, based on the mass of the thermoplastic polymer (B-1-III).

[0036] Methacrylic acid alkyl esters having an alkyl group with 1 to 8 carbon atoms (hereinafter referred to as methacrylic acid C 1-8 A preferred example of the alkyl ester is methyl methacrylate.

[0037] Methacrylic acid C that constitutes the thermoplastic polymer (B-1-III) 1-8 The amount of the monofunctional monomer units other than the alkyl ester is preferably from 0 to 20% by mass, more preferably from 5 to 15% by mass, based on the mass of the thermoplastic polymer (B-1-III). Methacrylic acid C 1-8 Examples of monofunctional monomers other than alkyl esters include acrylic esters such as methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, and propyl acrylate; and aromatic vinyl compounds such as styrene.

[0038] The outermost layer may be a single layer made of one kind of thermoplastic polymer (B-1-III) or a multilayer made of two or more kinds of thermoplastic polymers (B-1-III).

[0039] The amount of the thermoplastic polymer (B-1-III) is preferably 40 to 75 mass %, more preferably 45 to 68 mass %, and further preferably 50 to 60 mass %, based on the amount of the multilayer copolymer elastomer (B-1).

[0040] In one embodiment of the present invention, the layer of crosslinked elastic material which is the inner layer has an intermediate layer (inner shell) made of a crosslinked rubber polymer (B-1-II) and an inner layer (core) made of a crosslinked polymer (B-1-I) and in contact with and covering the intermediate layer. It is preferable that the inner layer and the intermediate layer of the crosslinked elastic material layer form a core and a shell.

[0041] The crosslinked polymer (B-1-I) comprises methyl methacrylate units, monofunctional monomer units other than methyl methacrylate, and polyfunctional monomer units.

[0042] The amount of methyl methacrylate units constituting the crosslinked polymer (B-1-I) is preferably 40 to 98.5% by mass, more preferably 45 to 95% by mass, based on the mass of the crosslinked polymer (B-1-I).

[0043] The amount of monofunctional monomer units other than methyl methacrylate constituting the crosslinked polymer (B-1-I) is 1 to 59.5% by mass, preferably 4.7 to 54.7% by mass, based on the mass of the crosslinked polymer (B-1-I). Examples of monofunctional monomers other than methyl methacrylate include acrylic esters such as methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, and propyl acrylate; and aromatic vinyl compounds such as styrene.

[0044] The amount of the polyfunctional monomer unit constituting the crosslinked polymer (B-1-I) is preferably 0.05 to 0.5% by mass, more preferably 0.1 to 0.3% by mass, based on the mass of the crosslinked polymer (B-1-I). Examples of the polyfunctional monomer include ethylene glycol dimethacrylate, propylene glycol dimethacrylate, triethylene glycol dimethacrylate, hexanediol dimethacrylate, ethylene glycol diacrylate, propylene glycol diacrylate, triethylene glycol diacrylate, allyl methacrylate, and triallyl isocyanurate.

[0045] The amount of the crosslinked polymer (B-1-I) is preferably 5 to 40% by mass, more preferably 7 to 35% by mass, and further preferably 10 to 30% by mass, based on the amount of the multilayer copolymer elastomer.

[0046] The crosslinked rubber polymer (B-1-II) comprises acrylate alkyl ester units having an alkyl group having 1 to 8 carbon atoms and / or conjugated diene units, and polyfunctional monomer units.

[0047] The amount of the acrylic acid alkyl ester units and / or conjugated diene units having an alkyl group having 1 to 8 carbon atoms constituting the crosslinked rubber polymer (B-1-II) is preferably 98.3 to 99 mass%, more preferably 98.4 to 98.8 mass%, based on the mass of the crosslinked rubber polymer (B-1-II).

[0048] Examples of the alkyl acrylate ester having an alkyl group having 1 to 8 carbon atoms include methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, and propyl acrylate.

[0049] Examples of conjugated dienes include 1,3-butadiene and isoprene.

[0050] Examples of the crosslinked rubber polymer (B-1-II) containing 1,3-butadiene as a monomer include 1,3-butadiene homopolymers and copolymers composed of 50% by weight or more of 1,3-butadiene units. Examples of such copolymers include butadiene-aromatic vinyl compound copolymers such as butadiene-styrene copolymers and butadiene-vinyltoluene copolymers, and further include terpolymers composed of 50% by weight or more of 1,3-butadiene units. These can usually be easily produced by known emulsion polymerization.

[0051] The amount of the polyfunctional monomer unit constituting the crosslinked rubber polymer (B-1-II) is preferably 1 to 1.7 mass %, more preferably 1.2 to 1.6 mass %, and even more preferably 1.3 to 1.5 mass %, based on the mass of the crosslinked rubber polymer (B-1-II). Examples of the polyfunctional monomer include those exemplified above.

[0052] From the viewpoint of improving flex resistance, the ratio (G / F) of the mass (G) of the polyfunctional monomer unit in the crosslinked polymer (B-1-I) to the mass (F) of the polyfunctional monomer unit in the crosslinked rubber polymer (B-1-II) is preferably 0.01 to 0.25, more preferably 0.05 to 0.2. The glass transition temperature of the crosslinked rubber polymer (B-1-II) is preferably lower than the glass transition temperature of the crosslinked polymer (B-1-I).

[0053] The amount of the crosslinked rubber polymer (B-1-II) is preferably 20 to 55 mass %, more preferably 25 to 45 mass %, and further preferably 30 to 40 mass %, based on the amount of the multilayer copolymer elastomer (B-1).

[0054] The multilayer copolymer elastomer has an average diameter (d) of the crosslinked elastic layer of preferably 60 to 110 nm, more preferably 65 to 105 nm, and even more preferably 70 to 100 nm. The average diameter d (nm) of the crosslinked elastic layer can be measured as follows. A resin composition (I) containing the multilayer copolymer elastomer is molded using a hydraulic press molding machine with a mold size of 50 mm x 120 mm, a press temperature of 250°C, a preheating time of 3 minutes, and a press pressure of 50 kg / cm. 2 , press time 30 seconds, cooling temperature 20℃, cooling pressure 50kg / cm 2The resulting plate is cut in a direction parallel to the long side at -100°C and cooled for 10 minutes to obtain a 40 nm thick slice, which is then stained with ruthenium. The stained slice is observed and photographed with a scanning transmission electron microscope (JEOL JSM7600F) at an accelerating voltage of 25 kV. The short and long diameters of the ruthenium-stained portion (exposed portion of the cross-linked elastic layer) are measured, and (short diameter + long diameter) / 2 is defined as the diameter of the cross-linked elastic layer. After measuring 20 or more pieces, the number average value (average diameter) is calculated.

[0055] The multi-layer copolymer elastomer may be produced by any method, including, for example, emulsion polymerization. In the case of emulsion polymerization, for example, a monomer (B-1-i) for constituting a crosslinked polymer (B-1-I) is emulsion polymerized to obtain a latex containing the crosslinked polymer (B-1-I), a monomer (B-1-ii) for constituting a crosslinked rubber polymer (B-1-II) is added thereto, and the monomer (B-1-ii) is seed emulsion polymerized to obtain a latex containing the crosslinked polymer (B-1-I) and the crosslinked rubber polymer (B-1-II), and a monomer (B-1-iii) for constituting a thermoplastic polymer (B-1-III) is added thereto, and the monomer (B-1-iii) is seed emulsion polymerized to obtain a latex containing a multilayer copolymer elastomer. Incidentally, emulsion polymerization is a known method used to obtain a latex containing a polymer. Seed emulsion polymerization is a method in which a polymerization reaction of a monomer is carried out on the surface of a seed particle. Seed emulsion polymerization is preferably used to obtain a core-shell structure polymer particle.

[0056] (Block copolymer elastomer (B-2)) The laminate of the present invention preferably contains, in the layer made of the resin composition (I), a block copolymer elastomer (B-2) consisting of a polymer block (b1) mainly having methacrylic acid ester units and a polymer block (b2) having acrylic acid ester units. The content of the block copolymer elastomer (B-2) in the resin composition (I) is preferably 1 to 49 mass%, more preferably 5 to 45 mass%, and further preferably 10 to 40 mass%. When the content of the block copolymer elastomer (B-2) is in the range of 1 to 49 mass%, the brittleness of the laminate of the present invention is improved.

[0057] The block copolymer elastomer (B-2) preferably comprises a polymer block (b1) mainly having methacrylic acid ester units and a polymer block (b2) having acrylic acid ester units. The block copolymer elastomer (B-2) may have only one polymer block (b1) in one molecule, or may have multiple polymer blocks (b1). Also, the block copolymer elastomer (B-2) may have only one polymer block (b2) in one molecule, or may have multiple polymer blocks (b2).

[0058] The amount of methacrylic acid ester units contained in the polymer block (b1) is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and even more preferably 98% by mass or more. As the methacrylic acid ester, for example, methyl methacrylate is preferable. The methacrylic acid ester can be used alone or in combination of two or more kinds in the polymer block (b1).

[0059] The amount of the polymer block (b1) contained in the block copolymer elastomer (B-2) is preferably from 40% by mass to 90% by mass, more preferably from 45% by mass to 80% by mass, from the viewpoints of transparency, flexibility, bending resistance, impact resistance, softness, moldability, surface smoothness, etc.

[0060] The glass transition temperature of the polymer block (b2) is preferably 20° C. or lower, more preferably −20° C. or lower.

[0061] The amount of acrylic acid ester units contained in the polymer block (b2) is preferably 90% by mass or more. Examples of acrylic acid esters include n-butyl acrylate and benzyl acrylate. These acrylic acid esters can be used alone or in combination of two or more in the polymer block (b2).

[0062] The polymer block (b2) may contain a monomer unit other than an acrylic ester, so long as it does not impede the object and effect of the present invention.

[0063] The polymer block (b2) preferably comprises an acrylic acid alkyl ester unit and a (meth)acrylic acid aromatic ester unit from the viewpoint of transparency, etc. The mass ratio of the acrylic acid alkyl ester unit / the (meth)acrylic acid aromatic ester unit is preferably 50 / 50 to 90 / 10, more preferably 60 / 40 to 80 / 20.

[0064] The bond form between the polymer block (b1) and the polymer block (b2) contained in the block copolymer elastomer (B-2) is not particularly limited. For example, a copolymer in which one end of the polymer block (b1) is bonded to one end of the polymer block (b2) (b1-b2 diblock copolymer) or a copolymer in which one end of the polymer block (b1) is bonded to each of both ends of the polymer block (b2) (b1-b2-b1 triblock copolymer) is preferred.

[0065] The block copolymer elastomer (B-2) has a weight average molecular weight of preferably 52,000 to 400,000, more preferably 60,000 to 300,000. The block copolymer elastomer also has a ratio of the weight average molecular weight to the number average molecular weight of preferably 1.01 to 2.00, more preferably 1.05 to 1.60. The weight average molecular weight and number average molecular weight of the block copolymer elastomer can be appropriately set from the viewpoints of moldability, tensile strength, appearance, etc. The weight average molecular weight and number average molecular weight are values ​​measured by GPC (gel permeation chromatography) in terms of standard polystyrene.

[0066] The block copolymer elastomer (B-2) is not particularly limited by its manufacturing method, and can be obtained by a known method. For example, a method including living polymerization of the monomers constituting each polymer block is generally used. As the living polymerization method, a method including anionic polymerization in the presence of an organic alkali metal compound and an organic aluminum compound is preferred, since it can obtain a high-purity block copolymer elastomer, and it is easy to control the molecular weight and composition ratio, and it is inexpensive. (Methacrylic resin (C)) The laminate of the present invention preferably contains a methacrylic resin (C) in the layer made of the resin composition (I). The content of the methacrylic resin (C) in the resin composition (I) is preferably 1 to 49% by mass, more preferably 5 to 45% by mass, and even more preferably in the range of 10 to 40% by mass. The flowability of the laminate of the present invention is improved by having the content of the methacrylic resin (C) in the range of 1 to 49% by mass.

[0067] The methacrylic resin (C) contains structural units derived from methyl methacrylate (hereinafter referred to as "MMA") in the total monomer units, preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass. When the methacrylic resin (A) contains structural units derived from MMA in an amount of 70% by mass or more, the surface hardness of the laminate of the present invention can be increased. The content of structural units derived from MMA in the methacrylic resin (C) can be calculated from the peak area ratio between the obtained MMA and the copolymerization components (mainly methyl acrylate) by subjecting the resin purified by reprecipitation of the methacrylic resin (C) in methanol to pyrolysis and separation of volatile components using pyrolysis gas chromatography.

[0068] The methacrylic resin (C) may contain structural units derived from monomers other than MMA among all monomer units. As such other monomers, methyl acrylate (hereinafter referred to as "MA") and ethyl (meth)acrylate are preferred from the viewpoint of availability. The total content of structural units derived from these other monomers in the methacrylic resin (C) is preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 10% by mass or less, and it is also preferred that the methacrylic resin does not contain structural units derived from monomers other than methacrylic acid esters.

[0069] The methacrylic resin (C) is obtained by polymerizing MMA alone or other optional monomers. In the case where multiple types of monomers are used in the polymerization, the multiple types of monomers are usually mixed to prepare a monomer mixture, which is then subjected to polymerization. There is no particular restriction on the polymerization method, but from the viewpoint of productivity, it is preferable to carry out radical polymerization by a method such as bulk polymerization, suspension polymerization, solution polymerization, or emulsion polymerization.

[0070] The lower limit of the syndiotacticity (rr) of the methacrylic resin (C) expressed by the triad is preferably 56% or more, more preferably 57% or more, and even more preferably 58% or more. When the lower limit of the content of such a structure is 56% or more, the resin composition (I) according to the present invention has excellent heat resistance.

[0071] Here, syndiotacticity (rr) expressed by a triad (hereinafter sometimes simply referred to as "syndiotacticity (rr)") is the proportion of two chains (diads, diads) in a chain of three consecutive structural units (triad) that are both racemo (denoted as rr). Note that in the chains (diads, diads) of structural units in a polymer molecule, those with the same stereoconfiguration are called meso, and those with the opposite stereoconfiguration are called racemo, and are denoted as m and r, respectively. The syndiotacticity (rr) (%) of the methacrylic resin (A) in deuterated chloroform at 30°C is 1The H-NMR spectrum is measured, and the area (Y) of the region from 0.6 to 0.95 ppm and the area (Z) of the region from 0.6 to 1.35 ppm are measured from the spectrum when tetramethylsilane (TMS) is set to 0 ppm, and the amount of the hydrogen can be calculated using the formula: (Y / Z) × 100.

[0072] The weight average molecular weight (hereinafter referred to as "Mw") of the methacrylic resin (C) is preferably 40,000 to 500,000, more preferably 60,000 to 300,000, and even more preferably 80,000 to 200,000. When the Mw is 40,000 or more, the resin composition (I) according to the present invention has excellent mechanical strength, and when it is 500,000 or less, the flowability is good.

[0073] The glass transition temperature of the methacrylic resin (C) is preferably 100° C. or higher, more preferably 105° C. or higher, and even more preferably 110° C. or higher. When the glass transition temperature is 100° C. or higher, the resin composition (I) according to the present invention has excellent heat resistance. In this specification, the glass transition temperature is a temperature measured using a differential scanning calorimeter at a heating rate of 10° C. / min and calculated by the midpoint method.

[0074] The saturated water absorption of the methacrylic resin (C) in 23°C water is preferably 2.5% by mass or less, more preferably 2.3% by mass or less, and even more preferably 2.1% by mass or less. When the saturated water absorption is 2.5% by mass or less, the resin composition (I) according to the present invention has excellent moisture resistance and can suppress warping of the laminate caused by moisture absorption. The saturated water absorption in this specification is a value measured by immersing a molded product in distilled water at 23°C, measuring the mass over time, and measuring the mass at the time of reaching equilibrium, relative to the mass of the molded product vacuum-dried for 3 days or more.

[0075] The melt flow rate (hereinafter, referred to as "MFR") of the methacrylic resin (C) is preferably in the range of 1 to 10 g / 10 min. The lower limit of the MFR is more preferably 1.2 g / 10 min or more, and even more preferably 1.5 g / 10 min or more. The upper limit of the MFR is more preferably 7.0 g / 10 min or less, and even more preferably 4.0 g / 10 min or less. When the MFR is in the range of 1 to 10 g / 10 min, the stability of the hot melt molding is good. In this specification, the MFR of the resin composition (I) according to the present invention is a value measured using a melt indexer at a temperature of 230°C under a load of 3.8 kg.

[0076] The resin composition (I) according to the present invention has a melt flow rate at 230° C. under a load of 3.8 kg of preferably 1 g / 10 min or more, more preferably 1.5 to 35 g / 10 min, and even more preferably 2 to 20 g / 10 min. The melt flow rate is a melt mass flow rate value measured in accordance with JIS K7210.

[0077] The resin composition (I) according to the present invention has a glass transition temperature of preferably 100 to 160° C., more preferably 105 to 155° C., and further preferably 110 to 150° C. If the glass transition temperature is below 100° C., the heat resistance tends to decrease, and if the glass transition temperature is above 160° C., the moldability tends to decrease.

[0078] The resin composition (I) according to the present invention has a saturated water absorption of 2.5% or less, more preferably 2.1% or less, and even more preferably 2.0% or less, measured under the same conditions as those for the saturated water absorption of the acrylic copolymer (A). The saturated water absorption of 2.5% or less provides excellent dimensional stability under high humidity conditions.

[0079] The resin composition (I) according to the present invention may contain a filler as necessary within a range that does not impair the effects of the present invention. Examples of the filler include calcium carbonate, talc, carbon black, titanium oxide, silica, clay, barium sulfate, magnesium carbonate, etc. The amount of the filler that can be contained in the resin composition (I) is preferably 3 mass% or less, more preferably 1.5 mass% or less.

[0080] The resin composition (I) according to the present invention may contain other polymers as long as the effects of the present invention are not impaired. Examples of other polymers include polyolefin resins such as polyethylene, polypropylene, polybutene-1, poly-4-methylpentene-1, and polynorbornene; ethylene-based ionomers; styrene-based resins such as polystyrene, styrene-maleic anhydride copolymer, high impact polystyrene, AS resin, ABS resin, AES resin, AAS resin, ACS resin, and MBS resin; methyl methacrylate-based polymers other than the acrylic copolymer (A), and methyl methacrylate-styrene copolymers; polyester resins such as polyethylene terephthalate and polybutylene terephthalate; polyamides such as nylon 6, nylon 66, and polyamide elastomers; polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, ethylene-vinyl alcohol copolymers, polyacetal, polyvinylidene fluoride, polyurethane, phenoxy resins, modified polyphenylene ethers, polyphenylene sulfide, and silicone-modified resins; silicone rubber; styrene-based thermoplastic elastomers such as SEPS, SEBS, and SIS; and olefin-based rubbers such as IR, EPR, and EPDM. The amount of other polymers is preferably 10% by mass or less, more preferably 5% by mass or less, and most preferably 0% by mass.

[0081] The resin composition (I) according to the present invention may contain additives such as antioxidants, heat deterioration inhibitors, ultraviolet absorbers, light stabilizers, lubricants, release agents, polymer processing aids, antistatic agents, flame retardants, dyes and pigments, light diffusing agents, organic dyes, matting agents, and fluorescent materials, as long as the effects of the present invention are not impaired.

[0082] The antioxidant is effective in preventing the oxidative deterioration of the resin by itself in the presence of oxygen. Examples of the antioxidant include phosphorus-based antioxidants, hindered phenol-based antioxidants, and thioether-based antioxidants. These antioxidants can be used alone or in combination of two or more. Among these, from the viewpoint of the effect of preventing the deterioration of optical properties due to coloring, phosphorus-based antioxidants and hindered phenol-based antioxidants are preferred, and the combined use of a phosphorus-based antioxidant and a hindered phenol-based antioxidant is more preferred. When the phosphorus-based antioxidant and the hindered phenol-based antioxidant are used in combination, their ratio is not particularly limited, but the mass ratio of the phosphorus-based antioxidant / the hindered phenol-based antioxidant is preferably 1 / 5 to 2 / 1, and more preferably 1 / 2 to 1 / 1.

[0083] Examples of phosphorus-based antioxidants include 2,2-methylenebis(4,6-di-t-butylphenyl)octyl phosphite (manufactured by ADEKA Corporation; trade name: Adeka STAB HP-10), tris(2,4-di-t-butylphenyl)phosphite (manufactured by Ciba Specialty Chemicals Corporation; trade name: IRUGA FOS 168), and 3,9-bis(2,6-di-tert-butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane (manufactured by ADEKA Corporation; trade name: Adeka STAB PEP-36).

[0084] Examples of the hindered phenol antioxidant include pentaerythrityl-tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] (manufactured by Ciba Specialty Chemicals; trade name IRGANOX1010) and octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate (manufactured by Ciba Specialty Chemicals; trade name IRGANOX1076).

[0085] The thermal degradation inhibitor is a compound that can prevent thermal degradation of a resin by capturing polymer radicals that are generated when the resin is exposed to high heat in a substantially oxygen-free state. Examples of the thermal degradation inhibitor include 2-t-butyl-6-(3'-t-butyl-5'-methyl-hydroxybenzyl)-4-methylphenyl acrylate (manufactured by Sumitomo Chemical Co., Ltd.; product name: Sumilizer GM) and 2,4-di-t-amyl-6-(3',5'-di-t-amyl-2'-hydroxy-α-methylbenzyl)phenyl acrylate (manufactured by Sumitomo Chemical Co., Ltd.; product name: Sumilizer GS).

[0086] An ultraviolet absorber is a compound that has the ability to absorb ultraviolet rays. An ultraviolet absorber is a compound that is said to have the function of converting light energy into heat energy. Examples of ultraviolet absorbents include benzophenones, benzotriazoles, triazines, benzoates, salicylates, cyanoacrylates, oxalic anilides, malonic acid esters, and formamidines. These may be used alone or in combination of two or more. Among these, benzotriazoles, triazines, or compounds having a maximum molar absorption coefficient εmax of 1200 dm at a wavelength of 380 to 450 nm are particularly preferred. 3 mol -1 cm -1 Preferred are UV absorbers which are:

[0087] As the benzotriazoles, 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol (manufactured by BASF; trade name TINUVIN329), 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (manufactured by BASF; trade name TINUVIN234), 2,2'-methylenebis[6-(2H-benzotriazol-2-yl)-4-tert-octylphenol] (manufactured by ADEKA; trade name LA-31), 2-(5-octylthio-2H-benzotriazol-2-yl)-6-tert-butyl-4-methylphenol, and the like are preferred.

[0088] In addition, when it is desired to efficiently absorb short wavelengths of 380 nm or less, triazine ultraviolet absorbers are preferably used. Examples of such ultraviolet absorbers include 2,4,6-tris(2-hydroxy-4-hexyloxy-3-methylphenyl)-1,3,5-triazine (manufactured by ADEKA; product name LA-F70), its analogues, hydroxyphenyltriazine ultraviolet absorbers (manufactured by BASF; product names TINUVIN477, TINUVIN460, and TINUVIN479), and 2,4-diphenyl-6-(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine.

[0089] The maximum molar absorption coefficient εmax of the ultraviolet absorber is measured as follows. 10.00 mg of ultraviolet absorber is added to 1 L of cyclohexane, and dissolved until no undissolved matter is found by visual observation. This solution is poured into a quartz glass cell measuring 1 cm x 1 cm x 3 cm, and the absorbance at wavelengths of 380 to 450 nm is measured using a spectrophotometer (Hitachi, Ltd.; product name U-3410). The molecular weight (M UV ) and the maximum value of the measured absorbance (Amax) are used to calculate the maximum molar absorption coefficient εmax according to the following formula. εmax=[Amax / (10×10-3)]×M UV

[0090] Light stabilizers are compounds that are said to have the function of capturing radicals generated mainly by oxidation due to light, and examples thereof include hindered amines such as compounds having a 2,2,6,6-tetraalkylpiperidine skeleton.

[0091] Examples of the lubricant include stearic acid, behenic acid, stearamide acid, methylene bisstearamide, hydroxystearic acid triglyceride, paraffin wax, ketone wax, octyl alcohol, and hardened oil.

[0092] The mold release agent is a compound having a function of facilitating the release of a molded product from a mold, and examples thereof include higher alcohols such as cetyl alcohol and stearyl alcohol, and higher fatty acid esters of glycerin such as monoglyceride stearate and diglyceride stearate. The use of higher fatty acid esters of glycerin may cause gel-like foreign matter, so it is preferable to use higher alcohols.

[0093] The polymer processing aid is a compound that is effective in achieving thickness accuracy and thinning when molding the resin composition (I). The polymer processing aid can usually be produced by an emulsion polymerization method. The polymer processing aid is preferably a polymer particle having a particle size of 0.05 to 0.5 μm. The polymer particles may be single-layer particles made of a polymer with a single composition ratio and a single intrinsic viscosity, or may be multi-layer particles made of two or more polymers with different composition ratios or intrinsic viscosities. Among these, preferred are particles with a two-layer structure having a polymer layer with a low intrinsic viscosity as an inner layer and a polymer layer with a high intrinsic viscosity of 5 dl / g or more as an outer layer. The polymer processing aid preferably has an intrinsic viscosity of 3 to 6 dl / g. If the intrinsic viscosity is too low, the effect of improving moldability is low. If the intrinsic viscosity is too high, the melt flowability of the resin composition (I) is likely to decrease.

[0094] Examples of the antistatic agent include alkylsulfonates such as sodium heptyl sulfonate, sodium octyl sulfonate, sodium nonyl sulfonate, sodium decyl sulfonate, sodium dodecyl sulfonate, sodium cetyl sulfonate, sodium octadecyl sulfonate, sodium diheptyl sulfonate, potassium heptyl sulfonate, potassium octyl sulfonate, potassium nonyl sulfonate, potassium decyl sulfonate, potassium dodecyl sulfonate, potassium cetyl sulfonate, potassium octadecyl sulfonate, potassium diheptyl sulfonate, lithium heptyl sulfonate, lithium octyl sulfonate, lithium nonyl sulfonate, lithium decyl sulfonate, lithium dodecyl sulfonate, lithium cetyl sulfonate, lithium octadecyl sulfonate, and lithium diheptyl sulfonate.

[0095] Examples of the flame retardant include metal hydrates having a hydroxyl group or crystal water, such as magnesium hydroxide, aluminum hydroxide, hydrated aluminum silicate, hydrated magnesium silicate, and hydrotalcite; phosphate compounds, such as polyamine phosphoric acid esters; and silicon compounds. Of these, preferred are phosphate ester-based flame retardants, such as trimethyl phosphate, triethyl phosphate, tripropyl phosphate, tributyl phosphate, tripentyl phosphate, trihexyl phosphate, tricyclohexyl phosphate, triphenyl phosphate, tricresyl phosphate, trixylenyl phosphate, dimethylethyl phosphate, methyl dibutyl phosphate, ethyl dipropyl phosphate, and hydroxyphenyl diphenyl phosphate.

[0096] Examples of dyes and pigments include red organic pigments such as para red, fire red, pyrazolone red, thioindigo red, and perylene red; blue organic pigments such as cyanine blue and indanthrene blue; and green organic pigments such as cyanine green and naphthol green. One or more of these may be used.

[0097] As the organic dye, a compound having a function of converting ultraviolet light into visible light is preferably used. Examples of the light diffusing agent and the matting agent include glass particles, polysiloxane-based crosslinked particles, crosslinked polymer particles, talc, calcium carbonate, and barium sulfate. Examples of fluorescent materials include fluorescent pigments, fluorescent dyes, fluorescent white dyes, fluorescent brighteners, and fluorescent bleaches.

[0098] These additives may be used alone or in combination of two or more. These additives may be added to the polymerization reaction solution when producing the acrylic copolymer (A) and the elastomer (B), or may be added to the produced acrylic copolymer (A) or the crosslinked rubber (B), or may be added when preparing the resin composition (I). From the viewpoint of suppressing defects in appearance of the molded article, the total amount of the additives is preferably 7% by mass or less, more preferably 5% by mass or less, and even more preferably 4% by mass or less, based on the resin composition (I).

[0099] (Resin composition (T)) The resin composition (T) used in the laminate of the present invention is a resin composition containing a polycarbonate. The polycarbonate is preferably obtained by copolymerizing a dihydric phenol such as bisphenol A with a carbonate precursor.

[0100] The Mw of the polycarbonate is preferably in the range of 10,000 to 100,000, and more preferably in the range of 20,000 to 70,000. When the Mw is 10,000 or more, the laminate of the present invention is excellent in impact resistance and heat resistance, and when the Mw is 100,000 or less, the polycarbonate is excellent in moldability, and the productivity of the laminate of the present invention can be increased.

[0101] The resin composition (T) may contain other polymers within the range that does not impair the effects of the present invention. As such other polymers, the same polymers as the methacrylic resin, the resin composition (I), and the other polymers that may be contained in the resin composition (I) described above can be used. These other polymers may be used alone or in combination of two or more. The content of these other polymers in the resin composition (T) is preferably 15% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less.

[0102] The resin composition (T) may contain various additives as necessary. The additives may be the same as those that may be contained in the resin composition (I). The content of these additives may be appropriately set within a range that does not impair the effects of the present invention, and it is preferable that the content of the antioxidant is 0.01 to 1 part by mass, the content of the ultraviolet absorber is 0.01 to 3 parts by mass, the content of the light stabilizer is 0.01 to 3 parts by mass, the content of the lubricant is 0.01 to 3 parts by mass, and the content of the dye or pigment is 0.01 to 3 parts by mass, relative to 100 parts by mass of the polycarbonate.

[0103] The resin composition (T) used in the present invention preferably has a glass transition temperature of 120 to 160° C. The resin composition (T) preferably has a glass transition temperature similar to that of the resin composition (I). Specifically, the absolute value |ΔTg| of the difference between the glass transition temperature of the resin composition (T) and the glass transition temperature of the resin composition (I) is preferably 30° C. or less, more preferably 20° C. or less. When |ΔTg| is 30° C. or less, the effect of suppressing the occurrence of warping of the laminate under high temperature and high humidity conditions is enhanced.

[0104] The resin composition (T) used in the present invention preferably has a saturated water absorption rate in water at 23°C of 0.1 to 1.0% by mass. The resin composition (T) preferably has a saturated water absorption rate similar to that of the resin composition (I). Specifically, the absolute value |Δsaturated water absorption rate| of the difference between the saturated water absorption rate of the resin composition (T) and the saturated water absorption rate of the resin composition (I) is preferably 2.0% by mass or less, more preferably 1.8% by mass or less. When the difference in saturated water absorption rate between the two resins is 2.0% by mass or less, the laminate is more effectively prevented from warping under high temperature and high humidity.

[0105] The MFR of the resin composition (T) used in the present invention is preferably in the range of 1 to 30 g / 10 min, more preferably in the range of 3 to 20 g / 10 min, and even more preferably in the range of 5 to 10 g / 10 min. When the MFR is in the range of 1 to 30 g / 10 min, the stability of hot melt molding is good. In this specification, the MFR of the resin composition (T) is measured using a melt indexer under conditions of a temperature of 300° C. and a load of 1.2 kg.

[0106] The polycarbonate may be a commercially available product. For example, Sumika Polycarbonate's "SD Polyca (registered trademark)", Mitsubishi Engineering Plastics Corporation's "Iupilon / Novarex (registered trademark)", Idemitsu Kosan Co., Ltd.'s "Toughlon (registered trademark)", Teijin Chemicals Co., Ltd.'s "Panlite (registered trademark)", and the like can be suitably used.

[0107] [Laminate] The laminate of the present invention may have a plurality of layers made of the resin composition (I) and / or layers made of the resin composition (T).

[0108] The laminate of the present invention may have a layer (another resin layer) made of another resin in addition to the layer made of the resin composition (I) and the layer made of the resin composition (T). Examples of the resin contained in the other resin layer include various thermoplastic resins other than the resin composition (I) and the resin composition (T); thermosetting resins; energy ray curing resins; and the like.

[0109] Examples of the other resin layers include an abrasion-resistant layer, an antistatic layer, an antifouling layer, a friction-reducing layer, an antiglare layer, an antireflection layer, an adhesive layer, and an impact strength-imparting layer.

[0110] The other resin layer may be one layer or more. When there are more than one other resin layers, they may be made of the same resin or different resins. In the laminate of the present invention, the order of arrangement of the other resin layers is not particularly limited, and they may be surface layers or inner layers.

[0111] From the viewpoint of producing the laminate of the present invention with good productivity while maintaining an excellent appearance, the thickness of the laminate is preferably in the range of 0.03 to 6.0 mm, more preferably in the range of 0.05 to 5.0 mm, and even more preferably in the range of 0.1 to 4.0 mm.

[0112] The thickness of the layer made of the resin composition (I) in the laminate of the present invention is preferably in the range of 0.01 to 0.6 mm, more preferably in the range of 0.015 to 0.5 mm, and even more preferably in the range of 0.02 to 0.4 mm. If the thickness is less than 0.01 mm, the scratch resistance and weather resistance may be insufficient. If the thickness exceeds 0.6 mm, the impact resistance may be insufficient.

[0113] The thickness of the layer made of the resin composition (T) in the laminate of the present invention is preferably in the range of 0.02 to 5.4 mm, more preferably in the range of 0.035 to 4.5 mm, and even more preferably in the range of 0.08 to 3.6 mm. If the thickness is less than 0.02 mm, the impact resistance may be insufficient. If the thickness exceeds 5.4 mm, the productivity may decrease.

[0114] The thickness of the layer made of the resin composition (I) in the laminate of the present invention is preferably in the range of 2 to 15% of the thickness of the laminate, more preferably in the range of 3 to 12%, and even more preferably in the range of 4 to 10%. If the thickness ratio is less than 2%, the scratch resistance and weather resistance may be insufficient. If it exceeds 15%, the impact resistance may be insufficient.

[0115] The thickness of the layer made of the resin composition (T) in the laminate of the present invention is preferably in the range of 85 to 98% of the thickness of the laminate, more preferably in the range of 88 to 97%, and even more preferably in the range of 90 to 96%. If the thickness ratio is less than 85%, the impact resistance may be insufficient. If it is 15% or more, the weather resistance may be insufficient.

[0116] When the laminate of the present invention has only a layer made of resin composition (I) and a layer made of resin composition (T), the layer made of resin composition (I) is represented as (1) and the layer made of resin composition (T) is represented as (2), and the stacking order of the laminate of the present invention can be (1)-(2); (1)-(2)-(1); (2)-(1)-(2); (1)-(2)-(1)-(2)-(1); etc., and from the viewpoint of improving scratch resistance, it is preferable that the laminate is stacked so that at least one surface is a layer made of resin composition (I), such as (1)-(2); (1)-(2)-(1); (1)-(2)-(1)-(2)-(1); etc.

[0117] Furthermore, when the laminate of the present invention has another resin layer, when such another resin layer is indicated as (3), the stacking order of the laminate of the present invention can be (1)-(2)-(3); (3)-(1)-(2); (3)-(1)-(2)-(3); (3)-(1)-(2)-(1)-(3); (1)-(2)-(3)-(2)-(1); etc. For example, when (3) is an abrasion-resistant layer, the stacking order of the laminate of the present invention, where the abrasion-resistant layer is represented as (3'), is preferably (3')-(1)-(2);(3')-(1)-(2)-(3'), (3')-(1)-(2)-(1)-(3'), etc., so that at least one surface is the abrasion-resistant layer.

[0118] Furthermore, when the laminate of the present invention has, in addition to (3), another resin layer different from (3), when the other resin layer different from (3) is denoted as (4), the stacking order of the laminate of the present invention can be (1)-(2)-(3)-(4); (4)-(3)-(1)-(2); (4)-(3)-(1)-(2)-(3); (4)-(1)-(2)-(3); (4)-(3)-(1)-(2)-(3)-(4); (4)-(3)-(1)-(2)-(1)-(3)-(4); and the like.

[0119] For example, when (3) is a scratch-resistant layer and (4) is an antireflective layer, with the antireflective layer represented as (4'), the layers are preferably laminated in the following order: (4')-(3')-(1)-(2); (4')-(3')-(1)-(2)-(3'); (4')-(3')-(1)-(2)-(3')-(4'); (4')-(3')-(1)-(2)-(1)-(3')-(4'); etc.

[0120] From the viewpoint of suppressing the occurrence of warping under high temperature and high humidity conditions, the laminate of the present invention preferably has a stacking order that is symmetrical in the thickness direction, and more preferably, the thicknesses of the layers are also symmetrical.

[0121] The total light transmittance of the laminate of the present invention is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more. When the total light transmittance is 80% or more, the laminate obtained by the present invention has excellent appearance quality. The total light transmittance can be measured by a method according to JIS K7105.

[0122] Although there is no particular limitation on the method for producing the laminate of the present invention, lamination of the layer made of the resin composition (I) and the layer made of the resin composition (T) is usually preferably performed by multi-layer molding. Examples of multi-layer molding include laminate molding methods such as multi-layer extrusion molding, multi-layer blow molding, multi-layer press molding, multi-color injection molding, and insert injection molding, and the like, and from the viewpoint of productivity, multi-layer extrusion molding is preferred.

[0123] Examples of methods for further laminating another resin layer include a method of forming a multilayer by the above-mentioned method together with a layer made of resin composition (I) and a layer made of polycarbonate, a method of applying another fluid resin to the surface of a previously prepared layer made of resin composition (I) or a layer made of resin composition (T) and drying or curing it, and a method of laminating a previously prepared layer made of resin composition (I) or a surface of resin composition (T) via an adhesive layer.

[0124] The method of multi-layer extrusion molding is not particularly limited, and a known multi-layer extrusion molding method used for producing multi-layer laminates of thermoplastic resins can be preferably used, and more preferably molding is performed using an apparatus equipped with a flat T-die and a polishing roll with a mirror-finished surface. In this case, the T-die method may be a feed block method in which the resin composition (I) and the resin composition (T) in a heated and molten state are laminated before flowing into the T-die, or a multi-manifold method in which the resin composition (I) and the resin composition (T) are laminated inside the T-die. From the viewpoint of improving the smoothness of the interface between the layers constituting the laminate, the multi-manifold method is preferred.

[0125] In this case, the polishing roll may be a metal roll or an elastic roll provided with a metal thin film on the outer periphery (hereinafter, may be referred to as a metal elastic roll). The metal roll is not particularly limited as long as it has high rigidity, and may be, for example, a drilled roll, a spiral roll, etc. The surface state of the metal roll is not particularly limited, and may be, for example, a mirror surface, or may have a pattern or unevenness. The metal elastic roll may be, for example, a substantially cylindrical rotatable shaft roll, a cylindrical metal thin film arranged to cover the outer periphery of the shaft roll and contact the film-like material, and a fluid sealed between the shaft roll and the metal thin film, and the metal elastic roll exhibits elasticity due to the fluid. The shaft roll is not particularly limited, and may be, for example, stainless steel. The metal thin film is, for example, stainless steel, and preferably has a thickness of about 2 to 5 mm. The metal thin film preferably has bending property, flexibility, etc., and preferably has a seamless structure without a welded joint. A metal elastic roll provided with such a metal thin film is excellent in durability, and if the metal thin film is mirror-finished, it can be handled in the same way as a normal mirror-finished roll, and if a pattern or irregularities are imparted to the metal thin film, it becomes a roll to which the shape can be transferred, making it easy to use.

[0126] The resin composition (I) and the resin composition (T) are preferably melt-filtered through a filter before and / or during multi-layer molding. By performing multi-layer molding using each melt-filtered resin composition, a laminate with few defects caused by foreign matter or gel can be obtained. There is no particular limitation on the filter material used, and it is appropriately selected depending on the temperature of use, viscosity, and filtration accuracy. For example, nonwoven fabric made of polypropylene, cotton, polyester, rayon, glass fiber, etc.; phenolic resin-impregnated cellulose film; sintered film of nonwoven metal fiber fabric; sintered film of powdered metal; wire mesh; or a combination of these can be used. Among them, it is preferable to use a plurality of sintered films of nonwoven metal fiber fabric laminated from the viewpoint of heat resistance and durability.

[0127] There are no particular limitations on the filtration accuracy of the filter, but it is preferably 30 μm or less, more preferably 10 μm or less, and even more preferably 5 μm or less.

[0128] The scratch-resistant layer will be described in detail below as an example of a layer made of another resin composition. In this specification, the scratch-resistant layer is a layer for increasing hardness in a pencil scratch test, and is preferably a layer that exhibits a hardness of "4H" or more in the pencil scratch test specified in JIS-K5600-5-4. The scratch-resistant layer is preferably provided on the surface of the layer made of the resin composition (I).

[0129] The thickness of the scratch-resistant layer is preferably 2 to 10 μm, more preferably 3 to 8 μm, and even more preferably 4 to 7 μm. When the thickness is 2 μm or more, scratch resistance tends to be maintained, and when the thickness is 10 μm or less, the impact resistance of the laminate tends to be excellent.

[0130] The scratch-resistant layer can be formed by applying a fluid curable composition made of a monomer, oligomer, resin, etc. to the surface of another layer (e.g., a layer made of resin composition (I) or a layer made of resin composition (T)) and curing it. These curable compositions are, for example, thermosetting compositions that are cured by heat, or energy ray curable compositions that are cured by energy rays such as electron beams, radiation, and ultraviolet rays.

[0131] Examples of the curable compound contained in the thermosetting composition include compositions containing a phenol resin, a urea resin, a diallyl phthalate resin, a melamine resin, a guanamine resin, an unsaturated polyester resin, a polyurethane resin, an epoxy resin, an aminoalkyd resin, a melamine-urea co-condensation resin, a silicon resin, and a polysiloxane resin. These thermosetting compositions may contain, as necessary, curing agents such as crosslinking agents and polymerization initiators, polymerization accelerators, etc. As curing agents, isocyanates, organic sulfonic acids, etc. are usually used for polyester resins and polyurethane resins, amines for epoxy resins, and peroxides such as methyl ethyl ketone peroxide and radical initiators such as azobisisobutyl ester for unsaturated polyester resins.

[0132] Examples of the curable compound contained in the energy ray-curable composition include oligomers and / or monomers having a polymerizable unsaturated bond such as an acryloyl group or a methacryloyl group, a thiol group, or an epoxy group in the molecule. From the viewpoint of improving scratch resistance, oligomers and / or monomers having a plurality of acryloyl groups or methacryloyl groups are preferred.

[0133] The energy ray curable composition may contain a photopolymerization initiator and / or a photosensitizer in addition to the curable compound. Examples of such photopolymerization initiators include carbonyl compounds such as benzoin methyl ether, acetophenone, 3-methylacetophenone, benzophenone, and 4-chlorobenzophenone; sulfur compounds such as tetramethylthiuram monosulfide and tetramethylthiuram disulfide; 2,4,6-trimethylbenzoyldiphenylphosphine oxide and benzoyldiethoxyphosphine oxide; and examples of photosensitizers include n-butylamine, triethylamine, and tri-n-butylphosphine.

[0134] In the curable composition, the content of these curable compounds is preferably in the range of 30 to 100 mass%, more preferably in the range of 40 to 95 mass%, and further preferably in the range of 50 to 95 mass%. These curable compounds may be used alone or in combination of two or more kinds.

[0135] The curable composition may contain, as necessary, additives such as a monofunctional monomer, an organic solvent, a leveling agent, an antiblocking agent, a dispersion stabilizer, an ultraviolet absorber, a light stabilizer, an antioxidant, an antifoaming agent, a thickener, a lubricant, an antistatic agent, an antifouling agent, an antifogging agent, a filler, a catalyst, etc. The content of these additives can be appropriately set within a range that does not impair the effects of the present invention.

[0136] Examples of the method for applying the curable composition include spin coating, dipping, spraying, slide coating, bar coating, roll coating, gravure coating, meniscus coating, flexographic printing, and screen printing.

[0137] Applications of the laminate of the present invention include, for example, sign parts and marking films such as advertising towers, stand signs, side signs, transom signs, and rooftop signs; display parts such as showcases, partitions, and store displays; lighting parts such as fluorescent light covers, mood lighting covers, lampshades, lighted ceilings, lighted walls, and chandeliers; interior parts such as furniture, pendants, and mirrors; architectural parts such as doors, domes, safety window glass, partitions, staircase wainscoting, balcony wainscoting, and roofs of leisure buildings; transportation parts such as aircraft windshields, pilot visors, motorcycle and motorboat windshields, bus shades, automobile side visors, rear visors, head wings, headlight covers, automobile interior parts, and automobile exterior parts such as bumpers; audio-visual nameplates and stereo covers. , television protective masks, vending machines, mobile phones, personal computers, and other electronic equipment parts; medical equipment parts such as incubators and X-ray parts; machine covers, instrument covers, experimental equipment, rulers, dials, observation windows, and other equipment-related parts; liquid crystal protection plates, light guide plates, light guide films, Fresnel lenses, lenticular lenses, front panels of various displays, diffusion plates, and other optical parts; road signs, information boards, curved mirrors, soundproof walls, and other traffic-related parts; other than these, greenhouses, large aquariums, box aquariums, bathroom parts, clock panels, bathtubs, sanitary products, desk mats, game parts, toys, musical instruments, face protection masks during welding, solar cell back sheets, flexible solar cell front sheets, decorative films; and surface materials used for personal computers, mobile phones, furniture, vending machines, bathroom parts, etc. EXAMPLES

[0138] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples.

[0139] Measurements of physical properties were carried out by the following methods.

[0140] (Weight average molecular weight) The weight average molecular weight (Mw) of the resin obtained in the manufacturing example was determined by the GPC method (gel permeation chromatography method). A sample solution was prepared by dissolving 4 mg of the resin to be measured in 5 ml of tetrahydrofuran. The temperature of the column oven was set to 40°C, and 20 μl of the sample solution was injected into the device at an eluent flow rate of 0.35 ml / min to measure the chromatogram. Ten standard polystyrene points with molecular weights in the range of 400 to 5,000,000 were measured by GPC, and a calibration curve showing the relationship between retention time and molecular weight was created. The Mw of the resin to be measured was determined based on this calibration curve. The value corresponding to the molecular weight of the standard polystyrene from the chromatogram measured by GPC was taken as the molecular weight of the copolymer. Equipment: Tosoh GPC equipment HLC-8320 Separation column: Tosoh Corporation's TSKguardcolum SuperHZ-H, TSKgel HZM-M, and TSKgel SuperHZ4000 connected in series Eluent: Tetrahydrofuran Eluent flow rate: 0.35mL / min Column temperature: 40℃ Detection method: Refractive index (RI)

[0141] (Composition of each unit in the copolymer) 1 The proton ratio of the phenyl group of the α-methylstyrene unit and the methoxy group of the methyl methacrylate unit was determined by H-NMR, and the α-methylstyrene unit was calculated from this.

[0142] (glass transition temperature Tg) The resin compositions obtained in the Production Examples were measured for their DSC curves in accordance with JIS K7121 using a differential scanning calorimeter (Shimadzu Corporation, DSC-50 (product number)) by heating them once to 250° C., then cooling them to room temperature, and then heating them from room temperature to 200° C. at a rate of 10° C. / min. The midpoint glass transition temperature determined from the DSC curve measured during the second heating was taken as the glass transition temperature in the present invention.

[0143] (Unit composition of acrylic copolymer) The α-methylstyrene units and styrene units had the same composition as those of the precursor polymer. 1 Using H-NMR (Bruker Corporation; product name ULTRA SHIELD 400 PLUS), the acrylic copolymer 1 H-NMR measurement was performed to determine the content (mol%) of each monomer unit in the acrylic copolymer, such as glutarimide units, methyl methacrylate units, and aromatic vinyl (α-methylstyrene and styrene) units, and the content (mol%) was converted to the content (weight%) using the molecular weight of each monomer unit.

[0144] (1% thermogravimetric reduction temperature) The resin composition obtained in the production example was heated at 10°C / min in a nitrogen atmosphere using a thermogravimetric analyzer (TGA-50, manufactured by Shimadzu Corporation), and the temperature at which the weight loss reached 1% was recorded as the 1% thermal weight loss temperature.

[0145] (saturated water absorption rate) The resin composition obtained in the Production Example was placed in a rectangular mold frame with a short side of 110 mm and a long side of 150 mm, and heated at 230°C and 50 kg / cm 2The sheet was pressed for 5 minutes to produce a sheet with a thickness of 2 mm, a short side of 110 mm, and a long side of 150 mm. The obtained sheet was cut into a square with a side of 50 mm to produce a test piece, which was then dried at 80°C under reduced pressure (1 kPa) for 24 hours, cooled in a desiccator at a temperature of 23°C and a relative humidity of 50%, and the mass was immediately measured and used as the initial mass. The test piece was then immersed in distilled water at 23°C to measure the mass over time, and the mass (absorbed mass) at the point where no mass change was observed was used to calculate the saturated water absorption rate according to the following formula. Saturated water absorption rate (%) = [(absorbed mass - initial mass) / initial mass] × 100

[0146] (Pencil hardness) The resin composition obtained in the Production Example was placed in a rectangular mold frame with a short side of 110 mm and a long side of 150 mm, and heated at 230°C and 50 kg / cm 2 The sheet was pressed for 5 minutes at 40°C for 5 minutes to produce a sheet with a thickness of 2 mm, short side of 110 mm, and long side of 150 mm. A moving table pencil scratch tester (Model P) (manufactured by Toyo Seiki Co., Ltd.) was used to press a pencil lead against the surface of the produced sheet at an angle of 45 degrees and a load of 500 g, and the presence or absence of scratches was confirmed. The hardness of the pencil lead was gradually increased, and the hardness of the lead one level softer than the point at which scratches were produced was recorded as the pencil scratch hardness.

[0147] (Moldability) The appearance of the laminates of the examples and comparative examples was visually observed, and the moldability was judged based on the presence or absence of bubbles or gel particles. 〇: No foaming or gel formation ×: Foaming or gel particles occur

[0148] (Dimensional stability) The laminates of the Examples and Comparative Examples were cut into rectangles with the long side parallel to the extrusion flow direction and the short side perpendicular to the extrusion flow direction to prepare test pieces with long sides of 200 mm and short sides of 120 mm. The test pieces were placed on a surface plate so that both ends of the test piece were in contact with the surface plate (i.e., so that the test piece was convex upward), and the maximum gap between the test piece and the surface plate was measured using a gap gauge to determine the initial warpage. Next, each test piece was left for 1 hour in a hot air dryer set at a temperature of 100°C, and then the test piece was hung with a clip on the short side in an environmental tester set at a temperature of 85°C and a relative humidity of 85%, and left in that state for 72 hours, and then cooled and humidified for 120 hours in an environment of 23°C and a relative humidity of 50%. As a result, all test pieces were warped in a bow shape along the long side of the test piece, with the layer made of resin composition (I) on the outside and the layer made of resin composition (T) on the inside. The test piece with such bow warpage was placed on a surface plate so that both ends were in contact with the surface plate (i.e., the test piece was convex upward), and the maximum value of the gap between the test piece and the surface plate was measured using a gap gauge, which was taken as the amount of warpage under high temperature and high humidity. The amount of warpage change under high temperature and high humidity was calculated from the following formula, and the dimensional stability was judged from the amount of change. Warpage change under high temperature and humidity = Warpage under high temperature and humidity - Initial warpage ◎: Warpage change under high temperature and humidity is 2 mm or less ○: Warpage change under high temperature and humidity is more than 2mm but less than 3mm ×: Warpage change under high temperature and high humidity is greater than 3 mm (Surface hardness) The laminates of the examples and comparative examples were cut into rectangles with the long side parallel to the extrusion flow direction and the short side perpendicular to the extrusion flow direction to prepare test pieces with long sides of 200 mm and short sides of 120 mm. Using a moving table pencil scratch tester (Model P) (manufactured by Toyo Seiki Co., Ltd.), the presence or absence of scratches was confirmed while pressing a pencil lead against the surface of the resin composition (I) side of the test piece at an angle of 45 degrees and a load of 500 g. The hardness of the pencil lead increased in sequence, and the hardness of the lead one level softer than the point at which the scratch occurred was taken as the pencil scratch hardness. ⊚: The resin composition (I) surface of the laminate has a pencil hardness of 3H or more ◯: The pencil hardness of the resin composition (I) surface of the laminate is 2H ×: The pencil hardness of the resin composition (I) surface of the laminate is H or less. (weather resistance) The laminates of the examples and comparative examples were cut into 50 mm × 50 mm to prepare test pieces. The surface of the test piece on the side of the resin composition (I) was subjected to irradiation with a super UV tester (Iwasaki Electric Co., Ltd., SUV-W161) at a black panel temperature of 83°C, a relative humidity of 50%, and an irradiation energy of 100 mW / cm. 2 The test piece was then removed from the tester, and the surface condition of the surface on which the resin composition (I) was formed was visually observed. The weather resistance was evaluated based on the presence or absence of cracks. ◯: No cracks were generated on the resin composition (I) surface of the laminate. ×: Cracks were generated on the resin composition (I) surface of the laminate.

[0149] (Precursor polymer) The precursor polymers Aa to Ag in this production example were produced by the following method. Precursor polymers Aa-Af Purified methyl methacrylate (MMA), α-methylstyrene, 2,2'-azobis(2-methylpropionitrile) (AIBN) and n-octyl mercaptan (n-OM) were charged in an autoclave equipped with a stirrer in the ratios shown in Table 1 and dissolved uniformly to obtain polymerization raw materials. The polymerization raw materials were continuously supplied from the autoclave at 1.5 kg / hr to a tank reactor controlled at a polymerization temperature of 120°C, and polymerization reaction was carried out by a bulk polymerization method with an average residence time of 3 hours, and a liquid containing an acrylic copolymer was continuously discharged from the tank reactor. The polymerization conversion rate was the value shown in Table 1. Next, the liquid discharged from the reactor was heated to 230°C and supplied to a twin-screw extruder controlled at 240°C. In the twin-screw extruder, volatile matters mainly composed of unreacted monomers were separated and removed, and the acrylic copolymer was extruded into strands. The strands were cut with a pelletizer to obtain precursor polymers Aa to Af. The weight average molecular weight Mw, the proportion of α-methylstyrene structural units, and the glass transition temperature Tg of the obtained precursor polymers Aa to Af were measured. The results are shown in Table 1. In this production example, the amount (mass %) of units derived from MMA is {100 - (mass % of units other than α-methylstyrene units)}, so it is not shown in Table 1.

[0150] Precursor polymer Ag An MS resin (a copolymer of methyl methacrylate (MMA) and styrene (St)) was produced according to the production method for copolymer (A) described in the section [Examples] of JP 2003-231785 A. By changing the mass ratio of MMA, St and t-dodecyl mercaptan (t-DM) charged in an autoclave, a precursor polymer Ag; Mw = 95,000, Tg = 116°C, and a content of styrene monomer units of 10 mass% was obtained. The MMA units of the precursor polymer Ag were 90 mass%.

[0151] <Examples of various materials> The methacrylic resin (C), styrene copolymer (S) and polycarbonate according to the present invention were prepared using the following materials. Methacrylic resin (C): Parapet made by Kuraray Co., Ltd. (Mw=90,000, MMA copolymerization ratio=99.3%, MA copolymerization ratio=0.7%, Tg=117℃, saturated water absorption rate=2.0%) Styrene copolymer (S-1): Denka Resifi (Mw=80,000, styrene / maleic anhydride / MMA=56% / 18% / 26%, Tg=137℃, saturated water absorption=0.8%) Styrene copolymer (S-2): XIRAN manufactured by POLYSCOPE (Mw=80,000, styrene / maleic anhydride=74% / 26%, Tg=160℃, saturated water absorption=0.3%) Polycarbonate: SD polycarbonate manufactured by Sumika Polycarbonate Co., Ltd. (Mw=50,000, Tg=150℃, saturated water absorption rate=0.3%)

[0152] Manufacturing Example 1 The precursor polymer [Aa] was fed at 2 kg / hr to the transport section of a twin-screw extruder (manufactured by Technobel Co., Ltd.; product name KZW20TW-45MG-NH-600) consisting of a transport section, a melt-kneading section, a devolatilizing section, and a discharge section, and the screw speed and temperature were set at 120 rpm and 250° C., respectively, and monomethylamine was injected at 0.10 kg / hr from the additive supply port of the twin-screw extruder in the melt-kneading section equipped with a kneading block, to react the precursor polymer [Aa] with monomethylamine. A reverse flight was installed on the screw at the end of the reaction zone. In the volatilizing section set at 20 Torr (about 2.7 kPa), by-products and excess monomethylamine were volatilized from the molten resin that had passed through the melt-kneading section, and discharged through a vent. The molten resin extruded as a strand from a die provided at the end of the discharge part of the twin-screw extruder was cooled in a water tank and then cut with a pelletizer to obtain a pellet-shaped acrylic copolymer (Aa-1).

[0153] The acrylic copolymer (Aa-1) was supplied at 1 kg / hr to the transport section of a twin-screw extruder (manufactured by Technobel Co., Ltd.; product name KZW20TW-45MG-NH-600) consisting of a transport section, a melt-kneading section, a devolatilizing section and a discharge section, and set at a screw speed of 100 rpm and a temperature of 230 ° C., and in the melt-kneading section in which the kneading block was installed, a liquid consisting of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected at 0.024 kg / hr, and the dimethyl carbonate was reacted with the acidic content (derived from carboxyl groups and acid anhydrides) remaining in the acrylic copolymer (Aa-1). A reverse flight was installed on the screw at the end of the reaction zone. In the volatilizing section set at 20 Torr (about 2.7 kPa), by-products and excess dimethyl carbonate were volatilized from the molten resin that had passed through the melt-kneading section, and were discharged through a vent. The molten resin extruded as a strand from a die provided at the end of the discharge part of the twin-screw extruder was cooled in a water tank and then cut with a pelletizer to obtain a pellet-shaped acrylic copolymer (Aa-2).

[0154] The acrylic copolymer (Aa-2) was supplied at 1 kg / hr to the transport section of a twin-screw extruder (manufactured by Technobel Co., Ltd.; product name KZW20TW-45MG-NH-600), which consisted of a transport section, a melt-kneading section, a devolatilization section, and a discharge section, and was set at a screw rotation speed of 100 rpm and a temperature of 230°C. In the volatilizing section set at 20 Torr (approximately 2.7 kPa), volatile matters such as unreacted substances were volatilized from the molten resin that had passed through the melt-kneading section, and discharged through a vent. The molten resin extruded as a strand from a die at the end of the discharge section of the twin-screw extruder was cooled in a water tank and then cut with a pelletizer to obtain a pellet-shaped acrylic copolymer (A-1). The content of glutarimide units (proportion of structural units (R)) in the acrylic copolymer (A-1) was 9 wt%. The content of methyl methacrylate units in the acrylic copolymer (A-1) was {(100-8)-2×9}=74 wt%. 100 parts by mass of an acrylic copolymer, 0.15 parts by mass of Kalcol 8098 (manufactured by Kao Corporation), and 0.9 parts by mass of Adeka STAB LA-31 (manufactured by ADEKA Corporation) were mixed together, melt-kneaded at 250°C in a twin-screw extruder having a shaft diameter of 20 mm, and extruded to obtain a pellet-shaped resin composition (I-1). The evaluation results are shown in Table 1.

[0155] Manufacturing Example 2 An acrylic copolymer (A-2) and a resin composition (I-2) were obtained in the same manner as in Production Example 1, except that the precursor polymer (Aa) was replaced by the precursor polymer (Ab), the amount of monomethylamine added was 0.07 kg / hr, and a liquid consisting of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected at 0.018 kg / hr. The evaluation results are shown in Table 1.

[0156] Production Example 3 An acrylic copolymer (A-3) and a resin composition (I-3) were obtained in the same manner as in Production Example 1, except that the precursor polymer (Aa) was replaced by the precursor polymer (Ab), the amount of monomethylamine added was 0.14 kg / hr, and a liquid consisting of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected at 0.036 kg / hr. The evaluation results are shown in Table 1.

[0157] Production Example 4 An acrylic copolymer (A-4) and a resin composition (I-4) were obtained in the same manner as in Production Example 1, except that the precursor polymer [Ac] was used instead of the precursor polymer [Aa], the amount of monomethylamine added was 0.07 kg / hr, and a liquid consisting of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected at 0.018 kg / hr. The evaluation results are shown in Table 1.

[0158] Production Example 5 The acrylic copolymer (A-5) and the resin composition (I-5) were obtained in the same manner as in Production Example 1, except that the precursor polymer (Ad) was used instead of the precursor polymer (Aa), the amount of monomethylamine added was 0.07 kg / hr, and a liquid consisting of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected at 0.008 kg / hr. The evaluation results are shown in Table 1. Production Example 6 The acrylic copolymer (A-6) and the resin composition (I-6) were obtained in the same manner as in Production Example 1, except that the precursor polymer (Aa) was replaced by the precursor polymer (Ae), the amount of monomethylamine added was 0.08 kg / hr, and a liquid consisting of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected at 0.008 kg / hr. The evaluation results are shown in Table 1. Production Example 7 The acrylic copolymer (A-7) and the resin composition (I-7) were obtained in the same manner as in Production Example 1, except that the precursor polymer (Aa) was replaced by the precursor polymer (Af), the amount of monomethylamine added was 0.03 kg / hr, and a liquid consisting of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected at 0.008 kg / hr. The evaluation results are shown in Table 1.

[0159] Production Example 8 An acrylic copolymer (A-8) and a resin composition (I-8) were obtained in the same manner as in Production Example 1, except that the amount of monomethylamine added was 0.30 kg / hr and a liquid consisting of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected at 0.075 kg / hr. The evaluation results are shown in Table 1.

[0160] Production Example 9 The acrylic copolymer (A-9) and the resin composition (I-9) were obtained in the same manner as in Production Example 1, except that the precursor polymer (Aa) was replaced by the precursor polymer (Ag), the amount of monomethylamine added was 0.07 kg / hr, and a liquid consisting of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected at 0.018 kg / hr. The evaluation results are shown in Table 1.

[0161] Manufacturing Example 10 An acrylic copolymer (A-10) and a resin composition (I-10) were obtained in the same manner as in Production Example 1, except that the precursor polymer (Aa) was replaced by the precursor polymer (Ag), the amount of monomethylamine added was 0.45 kg / hr, and a liquid consisting of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected at 0.125 kg / hr. The evaluation results are shown in Table 1.

[0162] Manufacturing Example 11 An acrylic copolymer (A-11) and a resin composition (I-11) were obtained in the same manner as in Production Example 1, except that the precursor polymer (Aa) was replaced by the precursor polymer (Ab), no additives were added, and the mixture was passed through the extruder. The evaluation results are shown in Table 1. [Table 1]

[0163] Manufacturing Example 12 Multilayer copolymer elastomer (B-1) In a reactor equipped with a stirrer, a thermometer, a nitrogen gas inlet tube, a monomer inlet tube and a reflux condenser, 1050 parts by mass of ion-exchanged water, 0.44 parts by mass of sodium polyoxyethylene tridecyl ether acetate and 0.7 parts by mass of sodium carbonate were charged, and the inside of the reactor was fully replaced with nitrogen gas. The inside temperature was then set to 80°C. 0.25 parts by mass of potassium persulfate was added thereto and stirred for 5 minutes. 245 parts by mass of a monomer mixture consisting of 95.4% by mass of methyl methacrylate, 4.4% by mass of methyl acrylate and 0.2% by mass of allyl methacrylate was continuously dropped into the mixture over a period of 60 minutes. After the dropwise addition, the polymerization reaction was continued for another 30 minutes so that the polymerization conversion rate was 98% or more. Next, 0.32 parts by mass of potassium persulfate was added to the reactor and stirred for 5 minutes. After that, 315 parts by mass of a monomer mixture consisting of 80.5% by mass of butyl acrylate, 17.5% by mass of styrene, and 2% by mass of allyl methacrylate was continuously added dropwise over 60 minutes. After the dropwise addition was completed, the polymerization reaction was continued for another 30 minutes so that the polymerization conversion rate was 98% or more. Next, 0.14 parts by mass of potassium persulfate was added to the reactor and stirred for 5 minutes. Then, 140 parts by mass of a monomer mixture consisting of 95.2% by mass of methyl methacrylate, 4.4% by mass of methyl acrylate, and 0.4% by mass of n-octyl mercaptan was continuously dropped over 30 minutes. After the dropwise addition was completed, the polymerization reaction was continued for another 60 minutes so that the polymerization conversion rate was 98% or more. By the above operations, a latex containing a multilayer copolymer elastomer was obtained. The latex was frozen and coagulated. It was then washed with water and dried to obtain a multilayer copolymer elastomer (B-1). The average particle size of the multilayer copolymer elastomer (B-1) was 0.2 μm. 80 parts by mass of acrylic copolymer (A-1), 20 parts by mass of multilayer copolymer elastomer (B-1), 0.15 parts by mass of Kalcol 8098 (manufactured by Kao Corporation), and 0.9 parts by mass of Adeka STAB LA-31 (manufactured by ADEKA Corporation) were mixed together, melt-kneaded at 250°C using a twin-screw extruder with a shaft diameter of 20 mm, and extruded to obtain a pellet-shaped resin composition (I-12). The evaluation results are shown in Table 2.

[0164] Manufacturing Example 13 Block copolymer Elasto (B-2) A 3m glass-lined tank with a jacket and stirrer that can be cooled with brine and whose interior has been degassed and replaced with nitrogen. 3 A reaction vessel was charged with 735 kg of dry toluene, 0.4 kg of hexamethyltriethylenetetramine, and 39.4 kg of a toluene solution containing 20 mol of isobutylbis(2,6-di-t-butyl-4-methylphenoxy)aluminum at room temperature, and further charged with 1.17 mol of sec-butyllithium. 35.0 kg of methyl methacrylate was added thereto, and the mixture was reacted at room temperature for 1 hour to obtain a methyl methacrylate polymer (polymer block (b1-1)) having a weight average molecular weight (hereinafter referred to as Mw(b1-1)) of 40,000. Next, while keeping the reaction vessel at -25°C, a mixture of 24.5 kg of n-butyl acrylate and 10.5 kg of benzyl acrylate was added dropwise over 0.5 hours to grow a polymer block (b2) consisting of a copolymer of n-butyl acrylate and benzyl acrylate from one end of the polymer block (b1-1), thereby obtaining a diblock copolymer elastomer (B-2) having a weight average molecular weight of 80,000. Since the weight average molecular weight of the polymer block (b1-1) was 40,000, the weight average molecular weight (Mw(b2)) of the polymer block (b2) was determined to be 40,000. The block copolymer elastomer (B-2) has a content of 50 mass% of the polymer block (b2) having an acrylic ester unit. 80 parts by mass of acrylic copolymer (A-1), 20 parts by mass of block copolymer elastomer (B-2), 0.15 parts by mass of Kalcol 8098 (manufactured by Kao Corporation), and 0.9 parts by mass of Adeka STAB LA-31 (manufactured by ADEKA Corporation) were mixed, melt-kneaded at 250°C using a twin-screw extruder with a shaft diameter of 20 mm, and extruded to obtain a pellet-shaped resin composition (I-13). The evaluation results are shown in Table 2.

[0165] Manufacturing Example 14 80 parts by mass of acrylic copolymer (A-1), 10 parts by mass of multilayer copolymer elastomer (B-1), 10 parts by mass of block copolymer elastomer (B-2), 0.15 parts by mass of Kalcol 8098 (manufactured by Kao Corporation), 0.9 parts by mass of Adeka STAB LA-31 (manufactured by ADEKA Corporation) were mixed, melt-kneaded at 250 ° C. with a twin-screw extruder with a shaft diameter of 20 mm, and extruded to obtain a pellet-shaped resin composition (I-14). The evaluation results are shown in Table 2.

[0166] Manufacturing Example 15 80 parts by mass of acrylic copolymer (A-1), 20 parts by mass of methacrylic resin (C) (Parapet HR-S, manufactured by Kuraray Co., Ltd.), 0.15 parts by mass of Kalcol 8098 (manufactured by Kao Corporation), and 0.9 parts by mass of Adeka STAB LA-31 (manufactured by ADEKA Corporation) were mixed together, melt-kneaded at 250°C using a twin-screw extruder with a shaft diameter of 20 mm, and extruded to obtain a pellet-shaped resin composition (I-15). The evaluation results are shown in Table 2.

[0167] Manufacturing Example 16 30 parts by mass of methacrylic resin (C), 70 parts by mass of styrene copolymer (S-1), 0.15 parts by mass of Kalcol 8098 (manufactured by Kao Corporation), and 0.9 parts by mass of Adeka STAB LA-31 (manufactured by ADEKA Corporation) were mixed together, melt-kneaded at 250°C in a twin-screw extruder with a shaft diameter of 20 mm, and extruded to obtain a pellet-shaped resin composition (I-16). The evaluation results are shown in Table 2.

[0168] Manufacturing Example 17 50 parts by mass of methacrylic resin (C), 50 parts by mass of styrene copolymer (S-2), 0.15 parts by mass of Kalcol 8098 (manufactured by Kao Corporation), and 0.9 parts by mass of Adeka STAB LA-31 (manufactured by ADEKA Corporation) were mixed together, melt-kneaded at 250°C in a twin-screw extruder with a shaft diameter of 20 mm, and extruded to obtain a pellet-shaped resin composition (I-17). The evaluation results are shown in Table 2. [Table 2]

[0169] Example 1 Polycarbonate pellets were continuously fed into a single-screw extruder with a shaft diameter of 50 mm, and extruded in a molten state at a cylinder temperature of 280°C. Meanwhile, pellets of resin composition (I-1) were continuously fed into a single-screw extruder with a shaft diameter of 30 mm, and extruded in a molten state at a cylinder temperature of 220°C. The molten polycarbonate and resin composition (I-1) were introduced into a junction block, laminated in a multi-manifold die set at 250°C, and extruded into a sheet shape to produce a 1000μm thick laminate formed of two layers: a layer (first layer) made of resin composition (I-1) with a thickness of 80μm and a layer (second layer) made of polycarbonate with a thickness of 920μm. The evaluation results of the laminate are shown in Table 3.

[0170] Example 2 A resin composition (I-1) was used instead of the resin composition (I-2) in Example 1, and a resin composition (I-2) was used in the same manner as in Example 1. 2 A laminate having a total thickness of 1000 μm was produced, which consisted of a layer of polycarbonate having a thickness of 920 μm and a layer of polycarbonate having a thickness of 920 μm. The evaluation results of this laminate are shown in Table 3.

[0171] Example 3 A laminate having a total thickness of 1000 μm, consisting of a layer of resin composition (I-3) having a thickness of 80 μm and a layer of polycarbonate having a thickness of 920 μm, was produced in the same manner as in Example 1, except that resin composition (I-3) was used instead of resin composition (I-1) in Example 1. The evaluation results of this laminate are shown in Table 3.

[0172] Example 4 A laminate having a total thickness of 1000 μm, consisting of a layer of resin composition (I-4) having a thickness of 80 μm and a layer of polycarbonate having a thickness of 920 μm, was produced in the same manner as in Example 1, except that resin composition (I-4) was used instead of resin composition (I-1) in Example 1. The evaluation results of this laminate are shown in Table 3.

[0173] Example 5 A laminate having a total thickness of 1000 μm, consisting of a layer of resin composition (I-5) having a thickness of 80 μm and a layer of polycarbonate having a thickness of 920 μm, was produced in the same manner as in Example 1, except that resin composition (I-5) was used instead of resin composition (I-1) in Example 1. The evaluation results of this laminate are shown in Table 3. Example 6 A laminate having a total thickness of 1000 μm, consisting of a layer of resin composition (I-6) having a thickness of 80 μm and a layer of polycarbonate having a thickness of 920 μm, was produced in the same manner as in Example 1, except that resin composition (I-6) was used instead of resin composition (I-1) in Example 1. The evaluation results of this laminate are shown in Table 3. Example 7 A laminate having a total thickness of 1000 μm, consisting of a layer of resin composition (I-12) having a thickness of 80 μm and a layer of polycarbonate having a thickness of 920 μm, was produced in the same manner as in Example 1, except that resin composition (I-12) was used instead of resin composition (I-1) in Example 1. The evaluation results of this laminate are shown in Table 3.

[0174] Example 8 A laminate having a total thickness of 1000 μm, consisting of a layer of resin composition (I-13) having a thickness of 80 μm and a layer of polycarbonate having a thickness of 920 μm, was produced in the same manner as in Example 1, except that resin composition (I-13) was used instead of resin composition (I-1) in Example 1. The evaluation results of this laminate are shown in Table 3.

[0175] Example 9 A laminate having a total thickness of 1000 μm, consisting of a layer of resin composition (I-14) having a thickness of 80 μm and a layer of polycarbonate having a thickness of 920 μm, was produced in the same manner as in Example 1, except that resin composition (I-14) was used instead of resin composition (I-1) in Example 1. The evaluation results of this laminate are shown in Table 3.

[0176] Example 10 A laminate having a total thickness of 1000 μm, consisting of a layer of resin composition (I-15) having a thickness of 80 μm and a layer of polycarbonate having a thickness of 920 μm, was produced in the same manner as in Example 1, except that resin composition (I-15) was used instead of resin composition (I-1) in Example 1. The evaluation results of this laminate are shown in Table 3.

[0177] Example 11 Polycarbonate pellets were continuously fed into a single-screw extruder with a shaft diameter of 50 mm, and extruded in a molten state at a cylinder temperature of 280°C. Meanwhile, pellets of resin composition (I-1) were continuously fed into a single-screw extruder with a shaft diameter of 30 mm, and extruded in a molten state at a cylinder temperature of 220°C. The molten polycarbonate and resin composition (I-1) were introduced into a junction block, laminated in a multi-manifold die set at 250°C, and extruded into a sheet shape to produce a 1000μm thick laminate formed of two layers: a layer (first layer) made of resin composition (I-1) with a thickness of 200μm and a layer (second layer) made of polycarbonate with a thickness of 800μm. The evaluation results of the laminate are shown in Table 3.

[0178] Example 12 Polycarbonate pellets were continuously fed into a single-screw extruder with a shaft diameter of 50 mm, and extruded in a molten state at a cylinder temperature of 280°C. Meanwhile, pellets of resin composition (I-1) were continuously fed into a single-screw extruder with a shaft diameter of 30 mm, and extruded in a molten state at a cylinder temperature of 220°C. The molten polycarbonate and resin composition (I-1) were introduced into a junction block, laminated in a multi-manifold die set at 250°C, and extruded into a sheet shape to produce a 3000μm thick laminate formed of two layers: a layer (first layer) made of resin composition (I-1) with a thickness of 50μm and a layer (second layer) made of polycarbonate with a thickness of 2950μm. The evaluation results of the laminate are shown in Table 3.

[0179] Comparative Example 1 A laminate having a total thickness of 1000 μm, consisting of a layer of resin composition (I-7) having a thickness of 80 μm and a layer of polycarbonate having a thickness of 920 μm, was produced in the same manner as in Example 1, except that resin composition (I-7) was used instead of resin composition (I-1) in Example 1. The evaluation results of this laminate are shown in Table 3.

[0180] Comparative Example 2 A laminate having a total thickness of 1000 μm, consisting of a layer of resin composition (I-8) having a thickness of 80 μm and a layer of polycarbonate having a thickness of 920 μm, was produced in the same manner as in Example 1, except that resin composition (I-8) was used instead of resin composition (I-1) in Example 1. The evaluation results of this laminate are shown in Table 3.

[0181] Comparative Example 3 A laminate having a total thickness of 1000 μm, consisting of a layer of resin composition (I-9) having a thickness of 80 μm and a layer of polycarbonate having a thickness of 920 μm, was produced in the same manner as in Example 1, except that resin composition (I-9) was used instead of resin composition (I-1) in Example 1. The evaluation results of this laminate are shown in Table 3.

[0182] Comparative Example 4 A laminate having a total thickness of 1000 μm, consisting of a layer of resin composition (I-10) having a thickness of 80 μm and a layer of polycarbonate having a thickness of 920 μm, was produced in the same manner as in Example 1, except that resin composition (I-10) was used instead of resin composition (I-1) in Example 1. The evaluation results of this laminate are shown in Table 3.

[0183] Comparative Example 5 A laminate having a total thickness of 1000 μm, consisting of a layer of resin composition (I-11) having a thickness of 80 μm and a layer of polycarbonate having a thickness of 920 μm, was produced in the same manner as in Example 1, except that resin composition (I-11) was used instead of resin composition (I-1) in Example 1. The evaluation results of this laminate are shown in Table 3.

[0184] Comparative Example 6 A laminate having a total thickness of 1000 μm, consisting of a layer of resin composition (I-16) having a thickness of 80 μm and a layer of polycarbonate having a thickness of 920 μm, was produced in the same manner as in Example 1, except that resin composition (I-16) was used instead of resin composition (I-1) in Example 1. The evaluation results of this laminate are shown in Table 3.

[0185] Comparative Example 7 A laminate having a total thickness of 1000 μm, consisting of a layer of resin composition (I-17) having a thickness of 80 μm and a layer of polycarbonate having a thickness of 920 μm, was produced in the same manner as in Example 1, except that resin composition (I-17) was used instead of resin composition (I-1) in Example 1. The evaluation results of this laminate are shown in Table 3. [Table 3]

[0186] As shown in Table 3, the laminates of the present invention (Examples 1 to 6, Examples 11 to 12) use resin compositions (I-1) to (I-6) containing an acrylic copolymer excellent in heat resistance and low water absorption, and therefore have a small difference in glass transition temperature and saturated water absorption rate compared to the resin composition (T) containing polycarbonate, and therefore have excellent dimensional stability. Furthermore, since the resin compositions have excellent thermal decomposition resistance and high pencil hardness, the laminates of the present invention have excellent moldability and surface hardness. Furthermore, they also have excellent weather resistance. The laminates of the present invention (Examples 7 to 10) contain an acrylic copolymer having excellent heat resistance, pencil hardness, and weather resistance, and therefore do not exhibit performance degradation even in resin compositions (I-12) to (I-15) to which an elastomer or methacrylic resin is added. In contrast, heat resistance and water absorption Inferior to The laminates (Comparative Examples 1 to 4) using the resin compositions (I-7) to (I-10) have poor dimensional stability. The laminate (Comparative Example 5) using the resin composition (I-11) with low thermal decomposition resistance has poor moldability. Furthermore, the laminates (Comparative Examples 6 and 7) using the resin compositions (I-16) and (I-17) containing a styrene copolymer have low surface hardness and poor weather resistance. [Industrial Applicability]

[0187] The laminate of the present invention has excellent appearance quality and is characterized by good dimensional stability and surface hardness, and is suitable for use as covers and housings for display devices, window materials and covers for the interior and exterior of vehicles, and the like.

Claims

1. A laminate comprising: a layer made of a resin composition (I) containing 51 mass% or more of an acrylic copolymer (A) having 30 to 87 mass% of methyl methacrylate units, 6 to 40 mass% of structural units (R) having at least one ring structure in the main chain selected from the group consisting of glutaric anhydride units and N-substituted or unsubstituted glutarimide units, and 7 to 30 mass% of α-methylstyrene units; and a layer made of a resin composition (T) containing a polycarbonate.

2. 2. The laminate according to claim 1, wherein the structural unit (R) is an N-substituted or unsubstituted glutarimide unit represented by formula (QI). 【Chemistry 1】 (In formula (QI), R 1 are each independently a hydrogen atom or a methyl group; R 2 is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring.

3. The laminate according to claim 1 or 2, characterized in that the resin composition (I) contains 1 to 49 mass% of a multilayer copolymer elastomer (B-1) having a methacrylic acid ester unit and an acrylic acid ester unit.

4. The laminate according to claim 1 or 2, characterized in that the resin composition (I) contains 1 to 49 mass% of a block copolymer elastomer (B-2) consisting of a polymer block (b1) having a methacrylic acid ester unit and a polymer block (b2) having an acrylic acid ester unit.

5. 3. The laminate according to claim 1, wherein the resin composition (I) contains 1 to 49% by mass of a methacrylic resin (C).

6. The laminate according to any one of claims 1 to 5, wherein the absolute value of the difference in glass transition temperature between the resin composition (I) and the resin composition (T) is 30°C or less, and the absolute value of the difference in saturated water absorption between the resin composition (I) and the resin composition (T) is 2% or less.

7. 7. The laminate according to claim 1, wherein the thickness of the layer made of the resin composition (I) is 2 to 15% of the total thickness of the laminate.

8. The laminate according to any one of claims 1 to 6, comprising a layer of the resin composition (I) on at least one surface.

9. The laminate according to any one of claims 1 to 8, further comprising an abrasion-resistant layer on at least one surface.

Citation Information

Patent Citations

  • Film suitable for protection of polarizing plate, polarizing plate protection sheet, and polarizing plate

    JP2004126546A

  • Scratch-resistant resin plate and its use

    JP2009248416A

  • Resin composition, molded item, optical film, polarizer protective film, and polarizing plate

    JP2011052198A

  • Synthetic resin laminate

    WO2011145630A1

  • Multilayer plate

    WO2014050136A1